ln(12-x)=lnx+ln(x-5)

Simple and best practice solution for ln(12-x)=lnx+ln(x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ln(12-x)=lnx+ln(x-5) equation:


Simplifying
ln(12 + -1x) = lnx + ln(x + -5)
(12 * ln + -1x * ln) = lnx + ln(x + -5)
(12ln + -1lnx) = lnx + ln(x + -5)

Reorder the terms:
12ln + -1lnx = lnx + ln(-5 + x)
12ln + -1lnx = lnx + (-5 * ln + x * ln)
12ln + -1lnx = lnx + (-5ln + lnx)

Reorder the terms:
12ln + -1lnx = -5ln + lnx + lnx

Combine like terms: lnx + lnx = 2lnx
12ln + -1lnx = -5ln + 2lnx

Solving
12ln + -1lnx = -5ln + 2lnx

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '5ln' to each side of the equation.
12ln + 5ln + -1lnx = -5ln + 5ln + 2lnx

Combine like terms: 12ln + 5ln = 17ln
17ln + -1lnx = -5ln + 5ln + 2lnx

Combine like terms: -5ln + 5ln = 0
17ln + -1lnx = 0 + 2lnx
17ln + -1lnx = 2lnx

Add '-2lnx' to each side of the equation.
17ln + -1lnx + -2lnx = 2lnx + -2lnx

Combine like terms: -1lnx + -2lnx = -3lnx
17ln + -3lnx = 2lnx + -2lnx

Combine like terms: 2lnx + -2lnx = 0
17ln + -3lnx = 0

Factor out the Greatest Common Factor (GCF), 'ln'.
ln(17 + -3x) = 0

Subproblem 1

Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(17 + -3x)' equal to zero and attempt to solve: Simplifying 17 + -3x = 0 Solving 17 + -3x = 0 Move all terms containing l to the left, all other terms to the right. Add '-17' to each side of the equation. 17 + -17 + -3x = 0 + -17 Combine like terms: 17 + -17 = 0 0 + -3x = 0 + -17 -3x = 0 + -17 Combine like terms: 0 + -17 = -17 -3x = -17 Add '3x' to each side of the equation. -3x + 3x = -17 + 3x Combine like terms: -3x + 3x = 0 0 = -17 + 3x Simplifying 0 = -17 + 3x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 2(5x-1)+3=7x-14 | | 4x-(x-1)=12+5(x-1) | | 6x+22=8x+30 | | 40+5x=50+3x | | -2x-5y=7 | | 40+5x=50 | | 18-3(4x+2)=7x-4(4x-1) | | 7x*8x^2=0 | | x^3-4x^2+x+5=0 | | x^3-4x^2+x+5=o | | -2(4x+1)=2(-4x-1) | | 3(3x-7)=2(3x+10) | | 9-2+7x=9+3x+2 | | x^3+13x^2+3x+10=0 | | 7x+8=18+5x | | (6+3x)2=48 | | 32+x=74-2x | | (4+2x)5=70 | | 16-2x=30-4x | | (4x-2)3=30 | | 1790=0.04x | | 2x/5x= | | 52=r*26 | | 2(5x+14)=33 | | -8(t-2)-(t+4)=9 | | 2x=7x-25 | | 3x=5x-1 | | 1.9=0.05x-98.40 | | 10-0.25(x+4)=0 | | 8x+15=5x | | 2002=0.05x-98.40 | | n=-98.40+0.05x |

Equations solver categories